The Possibility of Establishing the Ombudsman of the Republic of Poland as a Body for the Protection of Whistleblowers Reporting Violations of European Union Law. Constitutional Issues - Ożóg Michał (Studies in Logic, Grammar and Rhetoric, 2023)
The purpose of this article is to analyze the constitutional considerations of the possibility of establishing the Ombudsman as a body to receive reports of violations of the law under the authority of Directive Directive (EU) 2019/1937 of the European Parliament and of the Council of October 23, 2019 on the protection of whistleblowers. The results of the research lead to the conclusion of the possible admissibility of such a solution, but with the need for appropriate system changes. However, the author recommends entrusting this competence to a newly created body.